STUDY OF MECHANICAL PROPERTIES, MICROSTRUCTURE AND RESIDUAL STRESS BY X-RAY DIFFRACTION IN WELDED JOINTS OF DUPLEX STEEL UNS S 31803 BY COATED ELECTRODE - Souza, M. C. L.; Badaró, W. D.; Monine, V. I.; Ferreira, C. A. M.; Tapanes, N. C. O. (Revista de Engenharia Térmica, 2023)
Duplex stainless steels are widely used in the chemical, nuclear and oil and gas industries. They have an austenitic-ferritic microstructure, in equal parts. In this work, the impacts on the mechanical properties, on the metallographic behavior and the analysis of the residual stresses caused after the welding process by coated electrode were analyzed. In these analyses, a specimen produced from a 10 mm thick duplex sheet was welded, and tensile tests, micrography and residual stress analysis by x-ray diffraction were carried out. The tensile test results showed values higher than those required by the material’s manufacturing standard. The specimens broke in the base metal during the tests, indicating that the welding parameters were properly specified and applied to the specimen. The metallographic analysis showed an increase in the ferritic phase in the weld region, which makes this region susceptible to pitting corrosion in environments containing chlorides. Residual stress analysis showed tensile stresses in the weld bead, in the longitudinal and transverse directions, and in the HAZ and in the root compressive stresses in the transverse direction and tensile stresses in the longitudinal direction. These stresses must be considered in the design of equipment and structures manufactured from this steel and when using coated electrode welding, to avoid premature failure, especially fatigue failure.